microRNA-155 Is Decreased During Atherosclerosis Regression and Is Increased in Urinary Extracellular Vesicles During Atherosclerosis Progression - Fitzsimons, Stephen; Oggero, Silvia; Bruen, Robyn; McCarthy, Cathal; Strowitzki, Moritz J.; Mahon, Niall G.; Ryan, Nicola; Brennan, Eoin P.; Barry, Mary; Perretti, Mauro; Belton, Orina (Frontiers in Immunology, 2020)
Background: Atherosclerosis is a chronic inflammatory disease driven by macrophage accumulation in medium and large sized arteries. Macrophage polarization and inflammation are governed by microRNAs (miR) that regulate the expression of inflammatory proteins and cholesterol trafficking. Previous transcriptomic analysis led us to hypothesize that miR-155-5p (miR-155) is regulated by conjugated linoleic acid (CLA), a pro-resolving mediator which induces regression of atherosclerosis in vivo. In parallel, as extracellular vesicles (EVs) and their miR content have potential as biomarkers, we investigated alterations in urinary derived EVs (uEVs) during the progression of human coronary artery disease (CAD). Methods: miR-155 expression was quantified in aortae from ApoE-/- mice fed a 1% cholesterol diet supplemented with CLA blend (80:20, cis-9,trans-11:trans-10,cis-12 respectively) which had been previously been shown to induce atherosclerosis regression. In parallel, human polarized THP-1 macrophages were used to investigate the effects of CLA blend on miR-155 expression. A miR-155 mimic was used to investigate its inflammatory effects on macrophages and on ex vivo human carotid endarterectomy (CEA) plaque specimens (n=5). Surface marker expression and miR content were analyzed in urinary extracellular vesicles (uEVs) obtained from patients diagnosed with unstable (n=12) and stable (n=12) CAD. Results: Here we report that the 1% cholesterol diet increased miR-155 expression while CLA blend supplementation decreased miR-155 expression in the aorta during atherosclerosis regression in vivo. CLA blend also decreased miR-155 expression in vitro in human THP-1 polarized macrophages. Furthermore, in THP-1 macrophages, miR-155 mimic decreased the anti-inflammatory signalling proteins, BCL-6 and phosphorylated-STAT-3. In addition, miR-155 mimic downregulated BCL-6 in CEA plaque specimens. uEVs from patients with unstable CAD had increased expression of miR-155 in comparison to patients with stable CAD. While the overall concentration of uEVs was decreased in patients with unstable CAD, levels of CD45+ uEVs were increased. Additionally, patients with unstable CAD had increased CD11b+ uEVs and decreased CD16+ uEVs. Conclusion: miR-155 suppresses anti-inflammatory signalling in macrophages, is decreased during regression of atherosclerosis in vivo and is increased in uEVs from patients with unstable CAD suggesting miR-155 has potential as a prognostic indicator and a therapeutic target.